Simulation of residential rainwater harvesting systems in Barangay Daang Bakal, Mandaluyong City - Dy, Edgene T.
There has always been a constant problem with flooding in the Philippines, and it has affected the economy and the people a lot. An emerging problem in the form of water shortage is also slowly becoming apparent. Rainwater harvesting can potentially solve both of these problems. Studies in Korea have shown that the community-based rainwater harvesting system can be used to mitigate the floods, and also have other potential uses and savings. A survey was conducted to be able to determine how many people are interested in the system, and the planned usage. To be able to determine the effect of the system in Barangay Daang Bakal, the rational method and the SCS equation are used. The yield-afterspill algorithm was used to determine the reliability values for mUltiple variables, to be able to obtain the proper tank size. The 48-hour rainfall precipitation value during Typhoon Fung Wong was used for the simulation. Reliability values for different tank sizes and different demands are obtained. A total rainfall runoff reduction based on the chosen tank size and interested residents is also shown, along with a comparison with the rainfall runoff computed.